Photocatalytic selective hydrogenation of α, β-unsaturated aldehydes over oxygen vacancies enriched layered double hydroxide supported Co3O4 nanoparticles photocatalyst. (15th December 2022) - Zhang, Jin; Gao, Mengting; Zhu, Pengqi; Wang, Yunwei; Wang, Ruiyi; Zheng, Zhanfeng
Graphical Abstract: The oxygen vacancies of Co3 O4 /MgAl-LDH facilitate the adsorption of –CO groups and hinder the adsorption of –CC groups in cinnamaldehyde, which ensure the high selectivity of cinnamyl alcohol in the photocatalytic hydrogenation of cinnamaldehyde reaction. Highlights: Oxygen vacancies enriched Co3 O4 /LDH photocatalyst was developed using CoMgAl-LDH. Oxygen vacancies act as the adsorption and activation site for carbanyl group. Light irradiation promotes the activation of isopropanol to provide active H species. Abstract: The design of efficient photocatalyst for selective hydrogenation of α, β -unsaturated aldehydes to unsaturated alcohols is changeling. In this study, oxygen vacancy enriched MgAl-layered double hydroxide (MgAl-LDH) supported Co3 O4 nanoparticle photocatalysts are developed taking the advantage of the semi-memory effect of CoMgAl-LDH. Excellent photocatalytic performance was achieved with a 99 % cinnamaldehyde conversion and 98 % cinnamyl alcohol selectivity at 100 °C under visible light irradiation. The electron enriched Co3 O4 nanoparticles facilitated the activation of isopropanol to provide active H species under light irradiation. In situ DRIFTS and DFT calculation results suggest the oxygen vacancies of MgAl-LDH were beneficial to the terminal O adsorption of –CO group in cinnamaldehyde and ensure the high selectivity of cinnamyl alcohol. This study demonstrated a novel synthesis strategy of Co3 O4 nano-photocatalyst for the efficient selective hydrogenation under visible light irradiation.